The Influence of Work Performance Assessment on Employee Performance at PT. Dayton Motor Bali - Agape Anjumarito Panjaitan; Nabila Tijani Tharifah (Journal of Management and Business Innovations, 2025)
This study examines the influence of performance appraisal on employee performance at PT. Dayton Motor Bali using a quantitative associative approach. Data were collected from all 30 employees through a structured questionnaire with a five-point Likert scale and analyzed using simple linear regression. The findings indicate that performance appraisal has a positive and significant effect on employee performance. The results imply that fairness, objectivity, and transparency in appraisal systems contribute to enhancing employees' work outcomes and motivation. Theoretically, the study supports the integration of Equity and Expectancy Theories in explaining motivation through fair evaluation systems, while practically, it provides insights for improving transparent and data-driven appraisal mechanisms in organizations.Keywords: Employee Performance, Fairness, Human Resource Management, Objectivity, Performance Appraisal, Transparency